Competencies Optimization of the Social Worker in Tutelary Research in the MIMP, UPE Lima-2015 - Vegas Cárdenas, Carmen Violeta (2021)
This research is the product of professional experience in the Directorate of Tutelary Research (now the Directorate of Special Protection) in 2015, where the Social Worker function has been performed. Hence, its contents inquire about the influence and importance of the social aspect in the determination and impact of protection measures towards a child, girl or adolescent in an alleged state of abandonment, which is reflected in the identification of the Social worker competencies in this field of action. The theory that guides the procedures and the methodology used as well as the analysis of the information responds to the social sciences. Therefore, aspects such as history, economic and political influence are closely related when assessing the situation of children, with their problems as well as in their solutions.